Outcome of Haemopoietic Stem Cell Transplantation in 21 Patients With Alpha‐Mannosidosis - Šáhó, Robert; Formánková, Renata; Eisengart, Julie B.; Lund, Allan Meldgaard; Videbaek, Cecilie; Gürbüz, Berrak Bilginer; Özbek, Namık Yaşar; Jasmi, Fatma; Ješina, Pavel; Feillet, François; Pochon, Cécile; Guémann, Anne‐Sophie; et al. (Journal of inherited metabolic disease, 2025)
ABSTRACT The outcomes of alpha‐mannosidosis after hematopoietic stem cell transplantation (HSCT) are incompletely described. This retrospective multi‐center study evaluated the outcomes of patients who underwent HSCT for their alpha‐mannosidosis after 2010. Twenty‐one children (11 females) with enzymatically and/or genetically confirmed alpha‐mannosidosis, diagnosed at a mean age of 14 months (0–60 months), were included. The median age at HSCT was 3.9 years (10 months to 13.3 years) with a median follow‐up of 2.3 years (0.3–14.1 years). Seventy‐four percent (14/19) of patients received an unrelated graft while the rest had a matched sibling donor. Primary engraftment was reached in 17 of 21 patients; four patients required a second HSCT with successful subsequent engraftment. Nine patients had severe post‐HSCT infections, five patients developed acute graft‐versus‐host disease (GvHD) (> = grade II), and one patient had chronic GvHD. No patient died during follow‐up. Seven out of ten patients received enzyme replacement therapy both pre‐ and post‐HSCT. Among children with clinical symptoms, improvement was documented in hepatomegaly (40% of patients before HSCT, down to 10% after), recurrent infections (62%/30%), and hearing disorder (85%/65%). In 13 patients with developmental data, outcomes after HSCT suggested at least mild delays persisted post‐HSCT in the majority (85%), with some trends of higher functioning with earlier treatment. Findings suggest HSCT has shown notable improvements in safety and is associated with clinical benefit in alpha‐mannosidosis. Neurodevelopmental findings require longer‐term study to account for phenotypic diversity.